2010
DOI: 10.1128/aem.02538-09
|View full text |Cite
|
Sign up to set email alerts
|

7-Ketocholesterol Catabolism by Rhodococcus jostii RHA1

Abstract: Oxysterols from steroid autooxidation have numerous harmful effects, but their biodegradation is poorly understood. Microarrays were used to study mineralization of the most common oxysterol, 7-ketocholesterol (7KC), by Rhodococcus jostii RHA1. Growth on 7KC versus growth on cholesterol resulted in 363 differentially expressed genes, including upregulation of two large gene clusters putatively encoding steroid catabolism. Despite this difference, 7KC degradation required key genes involved in cholesterol degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…It is unclear why in RHA1 cluster 3 is more tightly downregulated in the absence of cholate than cluster 1 in the absence of cholesterol. It is interesting that cluster 3 was also upregulated during growth on 7-keto-cholesterol (7KC) (18). However, only genes in cluster 1 were shown to be essential for 7KC catabolism, and it was concluded that induction of cluster 3 by 7KC is likely gratuitous.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why in RHA1 cluster 3 is more tightly downregulated in the absence of cholate than cluster 1 in the absence of cholesterol. It is interesting that cluster 3 was also upregulated during growth on 7-keto-cholesterol (7KC) (18). However, only genes in cluster 1 were shown to be essential for 7KC catabolism, and it was concluded that induction of cluster 3 by 7KC is likely gratuitous.…”
Section: Discussionmentioning
confidence: 99%
“…To test this prediction, we investigated the phenotype of RHA017, an hsaA deletion mutant of RHA1 (30).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids were electroporated into RHA017 (30) and E. coli using a MicroPulser from Bio-Rad (Hercules, CA) with Bio-Rad 0.1-cm GenePulser Cuvettes. The hsaA (Rv3570c) and hsaB (Rv3567c) genes were amplified from Mtb H37Rv A, cholesterol is transformed to 3-hydroxy-9,10-seconandrost-1,3,5(10)-triene-9,17-dione (3-HSA) via previous enzymatic steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5␣-Cholestane (0.25 mM) was used as an internal standard. The extracts were derivatized at room temperature with 200 l bis(trimethylsilyl)trifluoroacetamide/trimethylchlorosilane and analyzed with an Agilent 6890 series gas chromatograph equipped with an HP-5ms 30-m by 0.25-mm capillary column (Hewlett-Packard) and an HP 5973 mass-selective detector (22). The gas chromatography conditions were as follows: the injector temperature was set at 280°C, the transfer line temperature was 290°C, and the flow rate was 1 ml min Ϫ1 with helium.…”
Section: Transporters For Reassimilation Of Cholate Metabolitesmentioning
confidence: 99%